Mycobacterium tuberculosis burden, multidrug resistance pattern, and associated risk factors among presumptive extrapulmonary tuberculosis cases at Dessie Referral Hospital, Northeast Ethiopia - Endalkachew Tedla; Getnet Ayalew; Feleke Mekonnen (Egyptian Journal of Chest Disease and Tuberculosis, 2020)
Background Tuberculosis (TB) represents one of the major challenges to global health. TB is usually classified based on the disease symptoms and the site of infection. Two types of clinical manifestation of TB are pulmonary tuberculosis (PTB) and extrapulmonary tuberculosis (EPTB). Objective This study aimed at determining Mycobacterium tuberculosis and multidrug-resistant tuberculosis (MDR-TB) burden among presumptive EPTB cases and associated risk factors at Dessie Referral Hospital, North West Ethiopia. Methods A cross-sectional study was conducted from February to April, 2018. A total of 337 presumptive EPTB cases in Dessie Referral Hospital were included using convenient sampling. Data were collected using a prestructured questionnaire. Body fluid specimens were collected and processed. Cytology, GeneXpert, and GenoType MTBDR plus Line Probe Assays were used for the detection of MTB and MDR-TB. Data were entered and cleared by Epi data version 3.1 and analyzed using SPSS, version 21. Multivariate analysis was done. P value less than 0.05 at 95% confidence interval was considered as statistically significant. Results The overall prevalence of EBTB using GeneXpert and cytopathological technique was 23.4, 27.3%, respectively. TB lymphadenitis (48 and 53.3%, respectively) was the dominant type followed by pleural (27 and 25%, respectively) and peritoneal (24% and 21.7%, respectively) by GeneXpert and cytology. The prevalence of MDR-TB was one (1.3%). Previous history of PTB (P<0.001) and HIV (P<0.001) were significantly associated with EPTB. Conclusion High prevalence of EPTB (27.3%) was reported, and 1.3% of them were MDR-TB. TB lymphadenitis was dominant. History of previous PTB and HIV was significantly associated with EPTB. Therefore, clinicians, public health professionals, and health programmers should give attention to EPTB case finding, treatment as well as prevention and control of EPTB by adhering guidelines of the ministry of health and WHO recommendations.